E-LEARNING BERBASIS WEBSITE PADA SLBN 1 PALANGKA RAYA - Sinana, Admi Rut; Sahay, Abertun Sagit (Jurnal Saintekom : Sains, Teknologi, Komputer dan Manajemen, 2021)
This e-learning website was built for students of SMPLB and SMALB on SLBN 1 Palangka Raya who have special needs in terms of hearing and moving. Teachers in the classroom more often use video and picture media, this is certainly not a problem when students are in class, but when students are at home and want to repeat the learning, of course this will be an obstacle. Based on thats problems, it is expected that this Palangkaraya SLBN 1 E-Learning Website can facilitate the teaching and learning process of overcoming these learning problems. Designing and building e-learning for students of Palangka Raya 1 SMPLB using the Waterfall software development method according to Sommerville (2011: 29-30) This website was built using PHP and SQLyog as a database processor and XAMPP as a web server. The testing method carried out on the website is a blackbox testing.